Parameters Investigation of Hair Dyeing Using Natural Extract from Henna Leaves, Sappan Heartwood, Butterfly Pea Flowers, Mangosteen Husk and Red Cabbage - Raksaphort, Supattra; Yenyaem, Kawinpob; Gluntang, Sutatib; Champati, Worrayut; Tammakeson, Pansiri; Ngogngam, Suputra; Suwancharoen, Sunisa (Recent Science and Technology, 2021)
Nowadays, hair coloring products have been sold in local markets. Most of them normally contain synthetic chemicals which can cause irritation, skin allergy, and carcinogen. Therefore, using natural hair dyes has become increasingly popular. In this research, the effect of natural mordant on dyeing process, the initial concentration of natural extract, the dyeing time, and the color persistency were investigated. The natural extracts were obtained from henna leaves, sappan heartwood, butterfly pea flowers, mangosteen husk, and red cabbage. The results showed that color obtained from bleached hair dyeing was uncorrelated with the mordant. Hair color intensity increased with an increase in initial extract concentration and hair dyeing duration. Color persistency of hair dyed with sappan heartwood and henna leaves extracts were about 2 and 1 month(s) for bleached hair and natural grey hair, respectively. Moreover, color persistency of 2 months, 1.5 months, and a week on bleached hair were obtained from butterfly pea flower, red cabbage, and mangosteen husk, respectively. However, the natural grey hair was unable to be dyed with these extracts due to the hair type. Compared with dried and damaged hair, it was harder to dye strong hair.